A selective and sensitive phthalimide-based fluorescent probe for hydrogen sulfide with a large Stokes shift. Issue 119 (17th November 2015) - Yang, Liu; Liu, Xingjiang; Gao, Li; Qi, Fengpei; Tian, Huihui; Song, Xiangzhi
Abstract : A phthalimide-based fluorescent probe for H2 S with a large Stokes shift has been developed. This probe displayed good selectivity and high sensitivity. Imaging intracellular H2 S by using this probe was successfully achieved in living cells. Abstract : A phthalimide-based fluorescent probe for hydrogen sulfide has been developed with high sensitivity and excellent selectivity. Upon treatment with hydrogen sulfide, this probe displays a strong fluorescence enhancement (196-fold) with a large Stokes shift (105 nm). Moreover, the potential application of using this probe in biological systems has been demonstrated by imaging hydrogen sulfide in living cells.